The Strength and Thermal Properties of Concrete containing Water Absorptive Aggregate from Well-Graded Bottom Ash (BA) as Partial Sand Replacement - Abdullah, M.J. (Elsevier Ltd, 2022)
Bottom ash (BA) is a hazardous waste material from power plant. The well-graded BA can be a good sand replacement material in concrete. This study presents strength and thermal properties of concrete containing high calcium and water absorptive fine aggregate from well-graded BA as partial sand replacement (control mix (CM) 0, BM5: 5, BM10: 10, BM15: 15, and BM20: 20). The workability of fresh concrete mixes was tested via slump test. The strength of the hardened concrete was assessed based on compressive strength, split tensile strength, and flexural strength. The thermal property was evaluated based on thermal conductivity test. The optimization of these model parameters was conducted via I-Optimal design. The workability of concrete mixes was reduced with an increase of well-graded BA due to high water absorption effect. The compressive strengths of all mixes reached more than 50 on 28th curing days with maximum strength by BM15 (49.0 MPa). The split tensile strengths showed one quadratic curve combining all mixes with maximum strength reached by BM10 (2.7 MPa). The flexural strength has slow growth exponential pattern with maximum strength by BM20 (6.0 MPA). The thermal conductivity values were steadily increased up to BM15 (2.44 W/mK) and reduced at BM20 (2.15 W/mK). The well-graded BA proportions (5 to 20) were not showing any significant effect on the thermal properties. The optimised model of compressive strength has the highest accuracy with percentage errors below 5 compared to other parameters. The optimal well-graded BA as sand replacement material was BM10 giving 47 MPa compressive strength, 2.7 MPa split tensile strength, 5.3 MPa flexural strength, and 2.1152 W/mK thermal conductivity. The highest positive correlation coefficients were obtained between compressive strength and thermal conductivity (R2: 0.921). Thus, the well-graded BA improved the strength properties providing a sustainable supply in concrete technology. Â© 2022 Elsevier Ltd